Effect of Fe Doping on Photocatalytic Dye-Degradation and Antibacterial Activity of SnO2 Nanoparticles. (9th May 2022) - Preethi, T.; Senthil, K.; Pachamuthu, M. P.; Balakrishnaraja, R.; Sundaravel, B.; Geetha, N.; Bellucci, Stefano
Abstract : A simple hydrothermal method is utilized to synthesize iron-doped tin oxide nanoparticles (Fe-SnO2 NPs) at various doping concentrations. The structural characterization using XRD, Raman, and FTIR measurements confirmed the incorporation of Fe ions into the SnO2 lattice without any deviation in the tetragonal crystal system of SnO2 nanoparticles. SEM and HRTEM images show the spherical-shaped nanoparticles with agglomeration. The values of interplanar spacing (d -value) calculated from the HRTEM lattice are consistent with the XRD results. Further, optical analysis revealed a red shift in the optical absorption band and a decrease in the band gap energy with an increase in Fe-dopant concentration. The decrease of PL emission peak intensity with Fe doping revealed the generation of singly charged oxygen vacancies. The H2 O2 -assisted photocatalytic degradation efficiency of Fe-SnO2 NPs investigated against crystal violet dye indicated an efficiency of 98% for 0.05 M Fe-SnO2 NPs within 30 minutes under visible light illumination. In addition, the effects of pH, scavengers, and reusability of the catalyst are tested. The antibacterial behavior of Fe-SnO2 NPs against Escherichia coli is examined by using the colony count method, and the inhibition rate was found to be 49, 65, 70, and 78% for pure, 0.01, 0.03, and 0.05 M Fe-SnO2 NPs, respectively.